Achieving long-term stable perovskite solar cells via ion neutralization. Issue 4 (29th March 2016) - Back, Hyungcheol; Kim, Geunjin; Kim, Junghwan; Kong, Jaemin; Kim, Tae Kyun; Kang, Hongkyu; Kim, Heejoo; Lee, Jinho; Lee, Seongyu; Lee, Kwanghee
Abstract : Corrosive ionic defects in perovskite films degrade perovskite solar cells (PSCs) and long-term stable PSCs are realized by neutralizing the defects. Abstract : Despite recent reports of high power conversion efficiency (PCE) values of over 20%, the instability of perovskite solar cells (PSCs) has been considered the most serious obstacle toward their commercialization. By rigorously exploring the self-degradation process of planar-type PSCs using typical metal electrodes (Ag or Al), we found that the corrosion of the metal electrodes by inherent ionic defects in the perovskite layers is a major origin of intrinsic device degradation even under inert conditions. In this work, we have developed a new concept of a chemical inhibition in PSCs using amine-mediated metal oxide systems and succeeded in chemically neutralizing mobile ionic defects through mutual ionic interaction. As a consequence, we realized planar-type PSCs with long-term stability that maintain nearly 80% of their initial PCEs even after 1 year (9000 h) of storage under nitrogen and 80% of their initial PCEs after 200 h in ambient conditions without any encapsulation.